Extracts from healing without. Issue 3 (December 2020) - Mathews, Timothy
Abstract : In a fine example of how critique can cast itself as lyrical essay (see also, on this, the interview with David Shields in this number of CounterText ) – and, thereby too, of evolving forms of what is now recognised through the term 'creative criticism' – Tim Mathews reflects in this piece on Antony Gormley's exhibition at the Royal Academy of Art in the autumn of 2019. The focus is on how Gormley's sculptures invite and stage awareness of individual and community reflection on, and participation in, art. Both wide-ranging and intimate, it valuably reflects on the relatability of Gormley's work and on the responsibilities distinct in the gaze (both one's own and others') upon art's dimensioning of the human – and the experientiality of that.